Promoting adolescent reproductive health through PIK-R formation: A case study at SMP Muhdasa Yogyakarta - Astuti, Dhesi Ari; Kurniati, Nurul; Rasyid, Erwin; Ningrum, Rhadika Wahyu Kurnia (Universitas Muhammadiyah Magelang, 2025)
Adolescents at SMP Muhdasa Yogyakarta face limited access to continuous reproductive health education due to the lack of a structured platform such as the Adolescent Reproductive Health Information and Counseling Center (PIK-R). Therefore, this community service activity aimed to enhance students’ knowledge and skills in reproductive health and to foster an environment that supports the development of quality adolescents. The program was implemented through a participatory approach focusing on initiating the establishment of a PIK-R based on the principle of “from, by, and for adolescents.” This included comprehensive education and training for prospective peer educators. Evaluation results demonstrated a significant increase in students’ knowledge regarding PIK-R and the role of peer educators, with the percentage of students possessing very good knowledge increasing from 8.43% to 12.05% after the intervention. These findings indicate that health education is effective in improving student understanding and has the potential to form groups capable of addressing adolescent reproductive health issues, creating a positive environment that supports proactive attitudes, and preventing risky sexual behaviors among adolescents at SMP Muhdasa.